Measuring Economy Wide Effects of Big Transport Projects : The Case of Georgia - Monsalve, Carolina (World Bank, Washington, DC, 2016)
Georgia is upgrading its principal highway, running for more than 350 kilometers between the Black Sea on its western border and Azerbaijan in the east, at a cost of about 2.3 billion US dollars, or nearly 14 percent of its 2014 Gross domestic product (GDP). Apart from the immediate effects of the construction (financed largely by international institutions), how much will this relatively large investment improve economic conditions in Georgia? Will it significantly reduce travel costs, and if so, how much of the gain will flow through to the whole economy? Answers to those types of questions are rarely quantified for infrastructure projects in developing countries, either because the projects are too small or the necessary country-specific model is lacking. The Georgia project offered a unique combination of circumstances that made the estimations feasible: (1) a large investment relative to the size of the economy; (2) an already existing model and dataset depicting how the sectors of Georgia’s economy interact; and (3) partial completion of the road upgrade that allowed a simulation of expected gains to be informed by actual interim outcomes.